The Urgency of Tolerance and Peace Values in The Educational Environment of Mahad Al-Zaytun - Rohmah, Siti Ngainnur; Islami, Bilat Nur; Nurmadhani, Wilda; Haekal, Muhammad; Roiddin, Farhan; Sidiq, Kholaif Aulia; Arrasyid, Muhammad Ikhwan; Fadillah, Muhammad Haikal (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2025)
The Indonesian state with its various cultures has millions of endemic characteristics in every corner. Starting from the diversity of languages, cultures, to religions and beliefs, Indonesia is an example of the unity of all diversity in unity. At least that's the dream contained in